Determinación del riesgo de precios de transferencia en el sector exportador de cacao en el Ecuador durante el periodo 2011-2014 - Barragán Vásquez, Luis Bolívar (2016)
Cocoa represents 1.9% of primary exports in Ecuador, growing from 2009 to 2014 68.5%, its products, cocoa beans and processed are mainly exported to the United States, the Netherlands and Mexico, the main exporter of cocoa beans in South America and the seventh largest producer worldwide, producing qualities such as CCN51, ASE, ASS, ASSS and ASSPs, set at different prices by the Ministry of Agriculture and Livestock (MAGAP), which uses as prices reference to stated in the New York Intercontinental Exchange (ICE futures) prices, so that cocoa is listed as a commodity or primary product, unlike other commodities exported by Ecuador, this has a market in which set prices according to supply and demand. The importance of the sector, leading to the sector to be studied to determine if there is a risk of transfer pricing, exports of cocoa beans, for this daily information FOB prices reported in the National Customs Service of Ecuador was used (SENAE), and the New York Intercontinental Exchange (ICE Future), to assess whether there is a risk of transfer pricing in the sector, for this the relationship between the FOB price of the local product was studied, and international prices, and using the methodology proposed by Cosín Ochaíta (2007), L. Curtis & Nutsubidze (2010) in which an estimate by OLS is used to determine the price ratio, assessed the existence of models of conditional variance ARCH or GARCH, for a ratio of more robust prices. Finally, as a result, it was determined that there is a risk of transfer pricing in the export sector of cocoa beans, specifically for the periods 2011, 2012 and 2014.